Writing up qulitative research ... better - Wolcott, Harry (Investigación y Educación en Enfermería, 2008)
The article contains the conference given by professor Harry Wolcott in May 2003 in Medellín for the presentation of the second edition in Spanish of his book Writing Up Qualitative Research. He asks why is always the second chapter of a written report the “Revision of Literature” and could it be something else instead? He proposes for chapter two to be “Linking Up” of literature, theory and method as an alternative to the traditional literature review, on demand, as necessary, instead of treating this activities as independent exercises. With respect to literature review readers want to be engaged immediately with the problem being addressed. References are critical in helping to analyse and to situate the problem and the research in a broad context. Making the link to theory should be next, but until it is quite clear what is the research interest and how it relates to the report. Finally, linking up through method, what readers want to know is how data was obtained or what are the bases for making inferences. In this manner the researcher may inform the reader since the beginning with enough detail about the problem, its context, the theory it t articulates to and the method.Key words: qualitative research, writing researchreports, report structure